Efektivitas Pupuk Organik Cair (POC) Nasi Basi Dan Air Cucian Beras Terhadap Berat Basah Tanaman (Fakultas Teknik, Universitas Brawijaya, 2025)
This Community Service Activity (PKM) aims to provide education on reducing the use of chemical fertilizers by utilizing household waste as liquid organic fertilizer. The area of RT 02 RW 01, Ngadilangkung Village, which is part of the Berseri Village Program, is characterized by an environment filled with various plants and a well-managed waste management system. The methods used in this PKM activity include observation, interviews, and mapping to understand the existing household waste management system in the area. This activity aims to increase public awareness of the importance of reducing the use of chemical fertilizers, which have negative environmental impacts. By utilizing household waste as liquid organic fertilizer, it is also hoped to improve environmental quality. The use of liquid organic fertilizer from household waste is not only environmentally friendly but also more economical and easily obtainable. This PKM activity not only educates the public on how to make liquid organic fertilizer but also provides practical training so that the community can implement it directly. There are 37 houses that have already recycled and 52 units that have not. Thus, this program aims to create a healthier and more sustainable environment and increase public awareness of the importance of proper waste management